Pengaruh Good Corporate Governance terhadap Manajemen Laba pada PT Herfinta F&P Kebun Aek Batu - Yungki Akbar; Nurlaila Nurlaila (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
A good company, one of which is a company that is able to present regulations for employees, performance is the result of the aspects that are rolled out and this happens on the policies that are set to be implemented later. PT. HERFINTA F&P Kebun Aek Batu implements good corporate governance as evidenced by the intensive morning apple activity and becomes a routine before starting work. It can be trusted that this is able to contribute between superiors and subordinates to carry out work in accordance with SOPs and what is expected. So that if the performance is good, the company's profits will automatically experience the same thing and reduce or even eliminate earnings management practices in the company. The research method is carried out with a qualitative approach with data analysis research collection. Data was collected by means of interviews and observations. The respondents of this research include Harvest Employees of PT. HERFINTA F&P Aek Batu Gardens, South Labuhanbatu Regency. Based on data analysis research, it is known that the results of the study show that the application of good corporate governance in this case the application of morning apples to provide work motivation to support employee performance so as to produce the appropriate/desired production.